Nonparametric identification of nonlinear dynamic systems - Kenderi, Gábor (KIT Scientific Publishing, 2018)
A nonparametric identification method for highly nonlinear systems is presented that is able to reconstruct the underlying nonlinearities without a priori knowledge of the describing nonlinear functions. The approach is based on nonlinear Kalman Filter algorithms using the well-known state augmentation technique that turns the filter into a dual state and parameter estimator, of which an extension towards nonparametric identification is proposed in the present work.
English
Keywords: nichtlineare dynamische System; Kalman Filter; nonlinear dynamic system; nonparametric identification; nichtparametrische Identifikation